Sexual Anxiety and Marital Satisfaction in Young Adult Men - Awaliyah, Ima Asri; Pratiwi, Pradipta Christy (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Marriage is a physical and mental relationship between a man and a woman as husband and wife in an effort to form a new harmonious life. Marriage will be successful when there is marital satisfaction. Marital satisfaction is influenced by anxiety factors in sexual intercourse, known as sexual anxiety. The purpose of this study was to determine the correlation between sexual anxiety and marital satisfaction in young adult men. The research method used is correlational quantitative research. The sampling technique used was purposive sampling consisting of 604 male participants in Indonesia aged 21 to 40 years and married. Measurements in this study used the Relationship Assessment Scale (RAS) to measure marital satisfaction consisting of 6 items with Cronbach's Alpha 0.789 and the Multidimensional Sexual Self-Concept Questionnaire (MSSCQ) to measure sexual anxiety consisting of 5 items with Cronbach's Alpha 0.958. Data analysis was conducted using Pearson Product Moment correlation technique. The results of the analysis showed a significant negative correlation (r = -0.160; p < 0.05) between sexual anxiety and marital satisfaction. The results also showed that the majority of participants' sexual anxiety was in the low category at 86.4% and the majority of participants' marital satisfaction was in the high category at 84.1%.Pernikahan adalah hubungan lahir batin antara laki-laki dan perempuan sebagai suami istri dalam upaya membentuk suatu kehidupan baru yang harmonis. Pernikahan akan berhasil ketika adanya kepuasan pernikahan. Marital satisfaction salah satunya dipengaruhi oleh faktor kecemasan dalam berhubungan seksual yang dikenal dengan sexual anxiety. Tujuan penelitian ini adalah untuk mengetahui korelasi antara sexual anxiety dengan marital satisfaction pada laki-laki dewasa muda. Metode penelitian yang digunakan adalah penelitian kuantitatif korelasional. Teknik sampling yang digunakan adalah purposive sampling yang terdiri dari 604 partisipan laki-laki di Indonesia berusia 21 sampai 40 tahun dan sudah menikah. Pengukuran dalam penelitian ini menggunakan Relationship Assessment Scale (RAS) untuk mengukur marital satisfaction yang terdiri dari 6 item dengan Cronbach’s Alpha 0.789 dan Multidimensional Sexual Self-Concept Questionnaire (MSSCQ) untuk mengukur sexual anxiety terdiri dari 5 item dengan Cronbach’s Alpha 0.958. Analisis data dilakukan menggunakan teknik korelasi Pearson Product Moment. Hasil analisis menunjukkan adanya korelasi negatif yang signifikan (r = -0.160; p < 0.05) antara sexual anxiety dengan marital satisfaction. Hasil penelitian juga menunjukkan bahwa sexual anxiety mayoritas partisipan berada di kategori rendah sebesar 86.4% dan marital satisfaction mayoritas partisipan berada di kategori tinggi sebesar 84.1%.